2006
DOI: 10.1021/ma052315a
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence Studies of Phenanthrene−Azomethyne Conjugated−Nonconjugated Multiblock Copolymer

Abstract: A Schiff base type polymer containing phenanthrene and an aliphatic spacer in the main chain was prepared, and its photophysical behavior in diluted and concentrated solutions as well as in film form was studied by steady-state fluorescence spectroscopy. These data indicated that ground-state fluorescent phenanthrene aggregates were present in the films. Time-resolved measurements in diluted conditions showed biexponential decay implying in different microenvironments around the chromophore. Theoretical simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
31
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 46 publications
(145 reference statements)
2
31
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8] Several of them are also electroluminescent materials. 1,[4][5][6][7][8][9] The backbone of fluorene-based polymers contains a rigidly planar biphenyl structure which can be functionalized in the C-9 position to enhance the polymer solubility.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…[1][2][3][4][5][6][7][8] Several of them are also electroluminescent materials. 1,[4][5][6][7][8][9] The backbone of fluorene-based polymers contains a rigidly planar biphenyl structure which can be functionalized in the C-9 position to enhance the polymer solubility.…”
Section: Introductionmentioning
confidence: 99%
“…28 Several reports indicated that this is a convenient approach since this methodology combines good data quality with reasonable computational effort. 3,29 The theoretically simulated spectra of some fluorene oligomers were compared with the experimental UV-Vis spectra of the poly(2,7-9,9'-dihexylfluorenedyil) (PHF, Scheme 1) in dilute solutions. The number of repeating units in the oligomers varied from n = 1 to n = 8 and for each one of these we obtained the optimized geometry, the dipole moment, the electronic energy levels and the correspondent simulated electronic absorption spectra.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations